Hot quark matter and (proto-) neutron stars - Malfatti, Germán (2019)
In the first part of this paper, we use a nonlocal extension of the three-flavor Polyakov-Nambu-Jona-Lasinio model, which takes into account flavor-mixing, momentum dependent quark masses, and vector interactions among quarks, to investigate the possible existence of a spinodal region (determined by the vanishing of the speed of sound) in the QCD phase diagram and determine the temperature and chemical potential of the critical end point. In the second part of the paper, we investigate the quark-hadron composition of baryonic matter at zero as well as nonzero temperature. This is of great topical interest for the analysis and interpretation of neutron star merger events such as GW170817. With this in mind, we determine the composition of proto-neutron star matter for entropies and lepton fractions that are typical of such matter. These compositions are used to delineate the evolution of proto-neutron stars to neutron stars in the baryon-mass versus gravitational-mass diagram. The hot stellar models turn out to contain significant fractions of hyperons and isobars but no deconfined quarks. The latter are found to exist only in cold neutron stars.